Green Micro-LED With a Bandwidth Exceeding 2 GHz for 9-Gbps Visible Light Communication Based on SNR Gap-Dependent Bit and Power Loading - Jin, Zuxin; Lin, Runze; Liu, Xuyang; Sun, Di; Liu, Bin; Tao, Tao; Xu, Feifan; Fang, Zhilai; Cui, Xugao; Tian, Pengfei (Journal of lightwave technology, 2025)
Visible light communication (VLC) possesses abundant spectrum resource and can be a promising candidate in the 6G network for its ability of combining positioning, lighting and communication. At present, the high-speed VLC is mainly based on blue and red light. The data rate of green light is still low. In order to develop the bandwidth and data rate of green micro-LEDs in wavelength division multiplexing (WDM) applications of VLC system, we designed high-bandwidth green micro-LEDs with high light output power. A 10- μ m green micro-LED achieved an E-E bandwidth and an E-O bandwidth up to 1.27 GHz and 2.19 GHz at a current density of 40 kA/cm ^{2} . In order to increase the light output power to milliwatts, whereas mostly maintaining the same bandwidth as single pixel, series-connected micro-LED array was fabricated. We also utilized a bit and power loading algorithm for VLC system, which can obtain high spectral efficiency below the 3.8 × 10^{-3} forward error correction (FEC) threshold by adopting signal-to-noise ratio (SNR) gap adjustment. Record data rates of 9.06 Gbps, 8.14 Gbps and 6.23 Gbps with bit error rates (BER) of 3.7 × 10^{-3} , 3.4 × 10^{-3} and 3.2 × 10^{-3} were achieved at 0.2 m, 1 m and 3 m, respectively. These are the highest data rates achieved by green micro-LED in free space, which will promote the applications of high-speed WDM in VLC.